NAT gene polymorphisms and susceptibility to Alzheimer's disease: identification of a novel NAT1 allelic variant - Budge Marc; Jonovska Vesna; Bell Peter; Johnson Nichola; Sim Edith (BMC, 2004)
Abstract Background Alzheimer's disease is multifactorial, having environmental, toxicological and genetic risk factors. Impaired folate and homocysteine metabolism has been hypothesised to increase risk. In addition to its xenobiotic-metabolising capacity, human arylamine N-acetyltransferase type-1 (NAT1) acetylates the folate catabolite para-aminobenzoylglutamate and is implicated in folate metabolism. The purpose of this study was to determine whether polymorphisms in the human NAT genes influence susceptibility to Alzheimer's disease. Methods Elderly individuals with and without Alzheimer's disease were genotyped at the polymorphic NAT1 (147 cases; 111 controls) and NAT2 (45 cases; 63 controls) loci by polymerase chain reaction-restriction fragment length polymorphism, and the genotype and allele frequencies were compared using the chi-squared test. Results Although a trend towards fast NAT2 acetylator-associated Alzheimer's disease susceptibility was indicated and the NAT1*10/1*10 genotype was observed only in cases of Alzheimer's disease (6/147, 4.1%), no significant difference in the frequency of NAT2 (p = 0.835) or NAT1 (p = 0.371) genotypes was observed between cases and controls. In addition, a novel NAT1 variant, NAT1*11B, was identified. Conclusions These results suggest that genetic polymorphisms in NAT1 and NAT2 do not influence susceptibility to Alzheimer's disease, although the increase in frequency of the NAT1*10 allele in Alzheimer's disease is worthy of further investigation. Due to its similarity with the NAT1*11A allele, NAT1*11B is likely to encode an enzyme with reduced NAT1 activity.